2014
DOI: 10.17017/j.fish.88
|View full text |Cite
|
Sign up to set email alerts
|

Effect of stocking densities on growth, production and survival rate of red tilapia in hapa at fish hatchery Chilya Thatta, Sindh, Pakistan

Abstract: Effect of stocking density on growth, production and survival of red tilapia (Oreochromis mossambicus × O. niloticus) were conducted in hapa for 60 days at Chilya Thatta. Tilapia fry (4.5±0.02 cm, 2.0±0.01 g) were stocked into hapa (4.5x2.4x1 m). Three treatments with two replicates were used: T1-200; T2-250 and T3-300 fry/hapa. Fry were fed twice a daily with pelleted feed containing 35% protein, 5% of total biomass. After 60 days, the highest growth were determined in T1 (49.8±0.0 g) while in T3 lowest growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
3
2
0
Order By: Relevance
“…The survival ratio of fishes in this study were remained same (100%) in both treatments (T1 and T2) as also described by (Daudpota et al, 2014;Saeed and Al-Nagaawy, 2013;Maniruzzaman, 2001).…”
Section: Water Qualitysupporting
confidence: 86%
See 2 more Smart Citations
“…The survival ratio of fishes in this study were remained same (100%) in both treatments (T1 and T2) as also described by (Daudpota et al, 2014;Saeed and Al-Nagaawy, 2013;Maniruzzaman, 2001).…”
Section: Water Qualitysupporting
confidence: 86%
“…The water quality range in current study was suitable for the survival of Nile tilapia and seabream fish species and similar range were mentioned during the experimentation on hybrid red tilapia (Oreochromis niloticus × O. mossambicus) and Nile tilapia (O. niloticus) by Daudpota et al (2014, Shah et al (2014), Narejo et al (2003Narejo et al ( , 2005Narejo et al ( , 2010, and Malik et al ( , 2019. Although, Boyd (1990) reported that water quality especially adequate dissolved oxygen (DO) level also useful for oxidizing ammonia to nitrate and maintain the healthy pH level in water.…”
Section: Water Qualitysupporting
confidence: 70%
See 1 more Smart Citation
“…A number of anatomical features determine the total absorptive surface area of the gastrointestinal tract. Taller, narrower, and regularly shaped villi and higher number of villi per unit area are indicators that the function of the intestinal villi is activated [32][33][34][35][36][37][38][39][40][41][42][43][44][45]; (Miles et al, 2006). In general, these villi provided large surface area for absorption of available nutrients [46][47][48][49][50][51][52][53][54][55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…To achieve this, recirculating aquaculture systems (RASs) have been widely implemented in Europe and the USA, especially indoors [2]. Maintaining water quality is pivotal in these systems [3][4][5][6][7], necessitating the continuous monitoring of parameters such as dissolved oxygen (DO) levels, water temperature (Temp), acidity, alkalinity (ALK), water clarity, total ammonia nitrogen (TAN), and nitrite nitrogen (NO 2 -N). Measurements involve field equipment and laboratory assessments, often requiring chemicals, instruments, labor, time, and expenses [8].…”
Section: Introductionmentioning
confidence: 99%